2016
DOI: 10.1111/tpj.13269
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of biomass partitioning, stem gene expression, cell wall biosynthesis, and sucrose accumulation during development of Sorghum bicolor

Abstract: Biomass accumulated preferentially in leaves of the sweet sorghum Della until floral initiation, then stems until anthesis, followed by panicles until grain maturity, and apical tillers. Sorghum stem RNA-seq transcriptome profiles and composition data were collected for approximately 100 days of development beginning at floral initiation. The analysis identified >200 differentially expressed genes involved in stem growth, cell wall biology, and sucrose accumulation. Genes encoding expansins and xyloglucan endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 100 publications
(147 reference statements)
2
112
2
1
Order By: Relevance
“…and among the cell types within a tissue (i.e., epidermal, xylem, phloem, fiber cells, etc. ; Hatfield et al, 1999; McKinley et al, 2016). Expression analysis across different tissues will provide important insight into the role of cell wall related genes in that particular tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and among the cell types within a tissue (i.e., epidermal, xylem, phloem, fiber cells, etc. ; Hatfield et al, 1999; McKinley et al, 2016). Expression analysis across different tissues will provide important insight into the role of cell wall related genes in that particular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis provides information on the tissue specific target genes for bioengineering purposes. A recent study of sorghum gene expression in pre- and post-anthesis stages of stem internodes showed differential expression of genes involved in growth, cell wall development and stem sugar accumulation (McKinley et al, 2016). CesA, Csls, callose synthases, XTHs, glucuroarabinoxylan biosynthetic genes, expansins, glucosyl hydrolases, pectin lyases/esterases, and lignin biosynthetic genes were among the major differentially expressed cell wall related genes (McKinley et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that high-sugar varieties of sugarcane and sweet sorghum are characterized by high SPS activity and low VIN activity (Liu et al, 2013;McKinley et al, 2016;Zhu et al, 1997). However, this is not applicable to TS, because SPS activity and gene expression levels in leaf sheaths did not differ significantly between TS and KH (Figures 4 and 5).…”
Section: Candidates For the Factor Responsible For The High Sugar Accmentioning
confidence: 99%
“…and sweet sorghum (Sorghum bicolor), which mainly accumulate soluble sugars in the stem (for reviews, see Bihmidine et al, 2013;Slewinski, 2012;Wang et al, 2013). Those studies identified key enzymes and transporters for sugar accumulation, such as sucrose-phosphate synthase (Botha & Black, 2000;Grof et al, 2007;Liu et al, 2013;Zhu et al, 1997), vacuolar acid invertase (Liu et al, 2013;McKinley et al, 2016;Zhu et al, 1997), and tonoplast sugar transporter (Bihmidine et al, 2016). However, sugar metabolism in rice stems has received less attention.…”
Section: Introductionmentioning
confidence: 99%